Dynamic competition between Cooper pair and spin density wave condensation - B. Decrausaz; M. Pikulski; O. Ivashko; N. B. Christensen; J. Choi; L. Udby; Ch. Niedermayer; K. Lefmann; H. M. Rønnow; J. Mesot; J. Ollivier; T. Kurosawa; et al. (Physical Review Research)
Quantum matter phases may coexist microscopically even when they display competing tendencies. A fundamental question is whether such a competition can be avoided through the elimination of one phase while the other one condenses into the ground state. Here, we present a high-resolution neutron spectroscopy study of the low-energy spin excitations in the high-temperature superconductor La_{1.855}Sr_{0.145}CuO_{4}. In the normal state, we find low-energy magnetic fluctuations at incommensurate reciprocal lattice positions where spin-density-wave order emerges at lower Sr concentration or at high magnetic fields. While these spin excitations are largely suppressed by the emergence of the superconducting spin gap, some low-energy magnetic fluctuations persist deep inside the superconducting state. We interpret this result in terms of a dynamic competition between superconductivity and magnetism, where superconductivity impedes the condensation of low-energy magnetic fluctuations through the formation of magnetically mediated Cooper pairs.